Case series of 17 patients with cholangiocarcinoma among young adult workers of a printing company in Japan. (13th January 2014) - Kubo, Shoji; Nakanuma, Yasuni; Takemura, Shigekazu; Sakata, Chikaharu; Urata, Yorihisa; Nozawa, Akinori; Nishioka, Takayoshi; Kinoshita, Masahiko; Hamano, Genya; Terajima, Hiroaki; Tachiyama, Gorou; Matsumura, Yuji; et al.
Abstract Background An outbreak of cholangiocarcinoma occurred among workers in the offset color proof‐printing department at a printing company in Japan. The aim of this study was to clarify the characteristics of the patients with cholangiocarcinoma. Methods This was a retrospective study conducted in 13 Japanese hospitals between 1996 to 2013. The clinicopathological findings of cholangiocarcinoma developed in 17 of 111 former or current workers in the department were investigated. Most workers were relatively young. Results The cholangiocarcinoma was diagnosed at 25–45 years old. They were exposed to chemicals, including dichloromethane and 1, 2‐dichloropropane. The serum γ‐glutamyl transpeptidase activity was elevated in all patients. Dilated intrahepatic bile ducts without tumor‐induced obstruction were observed in five patients. The cholangiocarcinomas arose from the large bile ducts. The precancerous or early cancerous lesions, such as biliary intraepithelial neoplasia and intraductal papillary neoplasm of the bile ducts, as well as non‐specific bile duct injuries, such as fibrosis, were observed in various sites of the bile ducts in all eight patients for whom operative specimens were available. Conclusions The present results showed that cholangiocarcinomas occurred at a high incidence in relatively young workers of a printing company, who were exposed to chemicals including chlorinated organic solvents.